2016
DOI: 10.3892/mco.2016.734
|View full text |Cite
|
Sign up to set email alerts
|

Capture of esophageal and breast cancer cells with polymeric microfluidic devices for CTC isolation

Abstract: The present study evaluated the capture efficiency of esophageal and breast cancer cells with a modified 'polymeric circulating tumor cells (CTC)-chip' microfluidic device, which was developed for the isolation of circulating tumor cells. Esophageal cancer cell lines KYSE150, KYSE220 and KYSE510, and breast cancer cell lines MCF7, SKBR3 and MDA-MB-231 were used for evaluation. The capture efficiencies of the esophageal cancer cell lines in phosphate-buffered saline (PBS) were ~0.9, irrespective of epithelial c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 27 publications
0
23
1
Order By: Relevance
“…The CTC chip allowed us to apply subsequent analyses, such as a mutational study of genes of interest. Ohnaga reported that the CTC chip was able to isolate EC cell lines spiked in whole blood, and that its recovery rate was over 70% [ 33 ]. Following the CTC chip, many kinds of microfluidic platforms have been developed, such as ClearCell FX, based on size, deformability, and inertia separation [ 34 ]; CTC-iChip, based on positive and negative enrichment with size-based separation [ 35 ]; IsoFlux, based on automated continuous flow with EpCAM beads [ 19 ]; magnetic sifter, based on vertical flow configuration [ 36 ]; and vortex, based on inertial microfluidics and laminar microscale vortices without a red blood cells (RBC) lysis buffer [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…The CTC chip allowed us to apply subsequent analyses, such as a mutational study of genes of interest. Ohnaga reported that the CTC chip was able to isolate EC cell lines spiked in whole blood, and that its recovery rate was over 70% [ 33 ]. Following the CTC chip, many kinds of microfluidic platforms have been developed, such as ClearCell FX, based on size, deformability, and inertia separation [ 34 ]; CTC-iChip, based on positive and negative enrichment with size-based separation [ 35 ]; IsoFlux, based on automated continuous flow with EpCAM beads [ 19 ]; magnetic sifter, based on vertical flow configuration [ 36 ]; and vortex, based on inertial microfluidics and laminar microscale vortices without a red blood cells (RBC) lysis buffer [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…The CTC-Chip [25,243], and the herringbone chip [244,245] have been proven effective to isolate CTCs with both high CTC purity (50-62%) [25,245] and high recovery rate (90-95%) [244,245]. There are several microfluidic devices designed to use positive selection strategy for proof-of-concept purpose [34,57,59,124,184,210, and for specific cancer in clinical trials, (e.g., breast [270,271], pancreas [272,273], ovarian [274], prostate [275], esophageal cancer [270], gastric [271], colorectal cancer [276], cancer of unknown primary [277]) and for mutational analysis [278]. Moreover, combined preparation using positive, negative, or label-free selection methods with microfluidic devices for better performance is also feasible and have been reported [93].…”
Section: Microfluidic-based Methods For the High Purity Ctc Isolationmentioning
confidence: 99%
“…have not generally addressed this issue. [ 15,16 ] Throughput, purity and recovery must all be considered when isolating rare cells from a much larger population of circulating cells, and microfluidic systems featuring small sample volume requirements, multiplexing capabilities and fast processing times, tend to meet such requirements. [ 17 ] Moreover, microfluidic approaches can capture live, rare cells such that further cellular, microscopic, or molecular analysis are feasible.…”
Section: Introductionmentioning
confidence: 99%